2018
DOI: 10.1002/path.5060
|View full text |Cite
|
Sign up to set email alerts
|

Richter transformation driven by Epstein–Barr virus reactivation during therapy‐related immunosuppression in chronic lymphocytic leukaemia

Abstract: The increased risk of Richter transformation (RT) in patients with chronic lymphocytic leukaemia (CLL) due to Epstein-Barr virus (EBV) reactivation during immunosuppressive therapy with fludarabine other targeted agents remains controversial. Among 31 RT cases classified as diffuse large B-cell lymphoma (DLBCL), seven (23%) showed EBV expression. In contrast to EBV tumours, EBV DLBCLs derived predominantly from IGVH-hypermutated CLL, and they also showed CLL-unrelated IGVH sequences more frequently. Intriguing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…It is also well documented that a small percentage (10–15%) of patients with CLL will undergo histological transformation into an aggressive form of DLBCL [ 11 , 12 , 13 , 14 ] referred to as Ritchter syndrome (RS). Recently, it was reported that RS might occur following aggressive therapy during CLL that results in the reactivation of EBV [ 17 ]. Therefore, it is possible that the CLL patients tested in this study and the study by de Sanjose et al [ 58 ] represent two subgroups one in which EBV is a negative prognostic factor for patients with CLL and a second subgroup in which EBV contributes to RS transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also well documented that a small percentage (10–15%) of patients with CLL will undergo histological transformation into an aggressive form of DLBCL [ 11 , 12 , 13 , 14 ] referred to as Ritchter syndrome (RS). Recently, it was reported that RS might occur following aggressive therapy during CLL that results in the reactivation of EBV [ 17 ]. Therefore, it is possible that the CLL patients tested in this study and the study by de Sanjose et al [ 58 ] represent two subgroups one in which EBV is a negative prognostic factor for patients with CLL and a second subgroup in which EBV contributes to RS transformation.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have implicated EBV in RS [ 15 , 16 ], a mechanistic relationship has not been determined. However, a recent study demonstrated that therapy related to immunosuppression in patients with CLL resulted in EBV reactivation, which drove RS and the formation of the ABC subtype DLBCL in some patients [ 17 ]. This study as well as a recent study of DLBCL [ 18 ] has suggested that products of lytic EBV may contribute to the development of these malignancies, but additional studies need to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…In RS, the large cells may represent a new neoplasm or they could emerge through the transformation of the original CLL clone, which might occur due to the EBV reactivation [ 105 ]. The association between EBV reactivation and the increased risk of RS development in CLL patients during immunosuppressive therapy was also reported [ 106 ]. The pathogenesis and course of CLL condition have been linked to EBV-induced STAT-5, which may be associated with the rise of the mortality rates among CLL carriers [ 107 ].…”
Section: CMV and Ebv Infection Impact In Patients With Hematologicmentioning
confidence: 98%
“…Moreover, it has recently been shown in an in vivo model that immunosuppressive therapy leads to the reactivation of Epstein-Barr virus in CLL xenografts, increasing the risk of DLBCL (Richter transformation). 53 The viral miRNA that correlate in our networks could be a marker of viral reactivation.…”
Section: Discussionmentioning
confidence: 93%